Scientific Opinion on the substantiation of a health claim related to "L‐tug lycopene" and reduction of blood LDL‐cholesterol pursuant to Article 14 of Regulation (EC) No 1924/2006. (26th February 2015) - ,; ,
Abstract: Following an application from Lycotec Ltd, submitted pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of the United Kingdom, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to "L‐tug lycopene" and reduction of blood low‐density lipoprotein (LDL)‐cholesterol. The food constituent that is the subject of the claim is L‐tug lycopene (i.e. Lyc‐O‐Mato ® embedded in fat‐rich matrices by a manufacturing process claimed as proprietary and confidential by the applicant). The Panel considers that the food constituent, L‐tug lycopene, which is the subject of the claim, is sufficiently characterised. The Panel considers that reduction of blood LDL‐cholesterol concentrations is a beneficial physiological effect. A reduction in blood LDL‐cholesterol concentrations reduces the risk of CHD. The Panel notes that the unpublished studies submitted to support the claim were exploratory in nature and insufficient information was provided to allow the scientific evaluation of these studies. The Panel concludes that a cause and effect relationship has not been established between the consumption of L‐tug lycopene and reduction of blood LDL‐cholesterol.